Thoracic epidural analgesia is not associated with improved survival after pancreatic aurgery: long-term follow-up of the randomized controlled PAKMAN trial - Klotz, Rosa; Ahmed, Azaz; Tremmel, Anja; Büsch, Christopher; Tenckhoff, Solveig; Dörr-Harim, Colette; Lock, Johan F.; Brede, Elmar-Marc; Köninger, Jörg; Schiff, Jan-Henrik; Wittel, Uwe A.; Hötzel, Alexander; et al. (Anesthesia & analgesia, 2025)
BACKGROUND: - Perioperative thoracic epidural analgesia (EDA) and patient-controlled intravenous analgesia (PCIA) are common forms of analgesia after pancreatic surgery. Current guidelines recommend EDA over PCIA, and evidence suggests that EDA may improve long-term survival after surgery, especially in cancer patients. The aim of this study was to determine whether perioperative EDA is associated with an improved patient prognosis compared to PCIA in pancreatic surgery. - METHODS: - The PAKMAN trial was an adaptive, pragmatic, international, multicenter, randomized controlled superiority trial conducted from June 2015 to October 2017. Three to five years after index surgery a long-term follow-up was performed from October 2020 to April 2021. - RESULTS: - For long-term follow-up of survival, 109 patients with EDA were compared to 111 patients with PCIA after partial pancreatoduodenectomy (PD). Long-term follow-up of quality of life (QoL) and pain assessment was available for 40 patients with EDA and 45 patients with PCIA (questionnaire response rate: 94%). Survival analysis revealed that EDA, when compared to PCIA, was not associated with improved overall survival (OS, HR, 1.176, 95% HR-CI, 0.809-1.710, P = .397, n = 220). Likewise, recurrence-free survival did not differ between groups (HR, 1.116, 95% HR-CI, 0.817-1.664, P = .397, n = 220). OS subgroup analysis including only patients with malignancies showed no significant difference between EDA and PCIA (HR, 1.369, 95% HR-CI, 0.932-2.011, P = .109, n = 179). Similar long-term effects on QoL and pain severity were observed in both groups (EDA: n = 40, PCIA: n = 45). - CONCLUSIONS: - Results from this long-term follow-up of the PAKMAN randomized controlled trial do not support favoring EDA over PCIA in pancreatic surgery. Until further evidence is available, EDA and PCIA should be considered similar regarding long-term survival.